Leptospira Seroprevalence in Domestic Dogs and Cats on the Caribbean Island of Saint Kitts - Nicola Pratt; Anne Conan; Sreekumari Rajeev (Veterinary Medicine International)
Leptospirosis is an important bacterial zoonotic disease that affects humans and many animal species. Knowledge of prevalence of Leptospira in a given geographic region supports the implementation of effective control/prevention programmes and thus reduces the transmission risks. This study provides Leptospira seroprevalence and serovar distribution in dogs and cats on the Caribbean island of Saint Kitts. Convenient serum samples from domestic dogs (n=101) and cats (n=50) were tested by the microscopic agglutination test (MAT) using 21 Leptospira serovars belonging to 17 serogroups. Seroprevalence was recorded at 73.2% in dogs (95% confidence interval CI: 62.5–80.1%). Agglutinating antibodies to Leptospira were present against 13 of the 21 serovars tested by MAT. The highest seroprevalence was observed for serovar Autumnalis (56.4%) followed by Icterohaemorrhagiae (27.7%), Canicola (17.8%), Djasiman (14.9%), Bratislava (11.9%), Pyrogenes (11.9%), and Pomona (7.9%). A very low seroprevalence (4%, 95% CI: 0.5–14%) was observed in cats. This data confirms that dogs in Saint Kitts have a high-level exposure to a diverse set of Leptospira serovars.